The effects of essential oil mouthrinses with or without alcohol on plaque and gingivitis: a randomized controlled clinical study - Michael C. Lynch; Sheila Cavalca Cortelli; James A. McGuire; Jane Zhang; Danette Ricci-Nittel; Carolyn J. Mordas; Davi Romeiro Aquino; Jose Roberto Cortelli (BMC, 2018)
Abstract Background The efficacy of several variants of essential oil mouthrinses has been studied extensively. This is the first study to compare the anti-plaque and anti-gingivitis efficacy of two marketed essential oil mouthrinses: one is an alcohol containing mouthrinse and the other one is an alcohol-free mouthrinse. Methods This examiner-blind, parallel-group study randomized subjects to three groups: 1) Mechanical Oral Hygiene (MOH) only; 2) MOH plus Alcohol-Containing essential oil Mouthrinse (ACM); 3) MOH plus Alcohol-Free essential oil Mouthrinse (AFM). Primary endpoint was whole-mouth mean Modified Gingival Index (MGI) at six months. Secondary endpoints included whole-mouth mean MGI at one and three months, and whole-mouth mean Plaque Index (PI) and whole-mouth mean Bleeding Index (BI) at one, three and six months. Safety assessments were conducted at all time points. Results A total of 370 subjects were enrolled; 348 subjects completed the study. After six months, subjects using essential oil mouthrinses with or without alcohol showed significant reduction (p < 0.001) in gingivitis (28.2% and 26.7%, respectively) and significant reduction (p < 0.001) in plaque (37.8% and 37.0%, respectively), compared to those performing MOH only. Significant reductions in MGI, PI, and BI (p < 0.001) were observed at one and three months and also at six months for mean BI. No statistically significant differences were observed for all measured indices between ACM and AFM groups at any time point. Both mouthrinses were well tolerated. Conclusions No significant differences were observed in the efficacy of ACM and AFM to reduce plaque and gingivitis, when used in addition to MOH, over six months. Trial registration The trial was registered on clinicaltrials.gov on November 30, 2016. The registration number is NCT02980497 .